THE EFFECTIVENESS OF MENTORING AND MONITORING CONSUMPTION OF FE TABLETS AND THEIR EFFECTS ON INCREASING HB LEVELS - Mamat Mamat; Lia Komalasari (Poltekkes Kemenkes Bandung, 2020)
80, 9% of young women who received Fe Tablets were 98.6% consuming < 52 Fe Tables. The factors are most related to the low consumption of iron tablets in students concerning digestive disorders, the influence of others, student aversion, and environmental situations. This study aims to determine the effectiveness of mentoring and monitoring in the administration of Fe Tablets and its effect on increasing Hb levels in adolescent girls. The design of this study used quasi-experiment, with the population in the study were young women whose samples were those who were anemic and had experienced a failure in Fe Tablets consumption. The sample is divided into two groups, namely 1 group (experimental) mentoring (guidance and direction individually) and monitoring (monitoring) of consumption of Fe Tablets and the second group (control) and monitoring without mentoring. Before and after the intervention, hemoglobin concentration was examined. The results of the study showed that mentoring and monitoring of additional blood supplementation (Fe Tablets) were effective in the behavior of consuming Fe Tablets in young women with an Exp (β) (OR) value of 5.36 and p = 0.008. Consumption rates of Fe tables were more elevated in Hb levels compared to those with less Fe Tablets consumption levels. However, there was no relationship between Fe Tablets consumption and increased Hb levels.